Development of intravascular large B-cell lymphoma during prophylactic antibiotic treatment for anti-interferon-gamma autoantibody syndrome: A case report. Issue 11 (November 2022) - Tanigaki, Tomomi; Kimizuka, Yoshifumi; Maki, Yohei; Sato, Chikako; Yoshimatsu, Shinya; Ogata, Hiraku; Nomura, Sakika; Nishimura, Masashi; Serizawa, Yusuke; Ito, Koki; Igarashi, Shunya; Kurata, Yuhei; et al.
Abstract: Anti-interferon (IFN)-γ autoantibody-positive syndrome is one of the acquired non-HIV cellular immunodeficiencies, caused by abnormalities in the IFN-γ/interleukin (IL)-12 pathways. It is often diagnosed alongside the onset of disseminated mycobacterium infection, and requires continuous antimycobacterial chemotherapy; however, the detailed pathological mechanisms underlying this syndrome, including its prognosis, are not known. To the best of our knowledge, this is the first reported case of intravascular large B-cell lymphoma complicated by anti-IFN-γ autoantibody syndrome, presented in an 82-year-old woman. The patient had been diagnosed with anti-IFN-γ autoantibody immunodeficiency ten years ago. She had repeated subacute fever of undetermined origin for 13 months that made us suspect infections, such as disseminated mycobacterium disease and other viral and fungal infections, despite receiving prophylactic antimycobacterial chemotherapy with rifampicin and clarithromycin. However, all the screenings performed showed no evidence of infectious diseases; thus, she was finally diagnosed with intravascular large B-cell lymphoma via a random skin biopsy. Unfortunately, the patient debilitated rapidly and died. Evidence supporting a correlation between anti-IFN-γ autoantibody syndrome and carcinogenesis is still lacking, although it is known that patients with anti-IFN-γ autoantibody syndrome are at risk of persistent viral infection-related and T-cell lineage-related carcinogenesis. This case demonstrated that patients with anti-IFN-γ autoantibody syndrome are also at risk of developing B-cell lymphoma, such as intravascular lymphoma. This emphasizes that caution should be paid to increased risk of developing malignancy during the long-term management of anti-IFN-γ autoantibody syndrome with cellular immunodeficiency.